Successful treatment of early-onset Morganella morganii sepsis in an extremely low birth weight infant - Chia-Ning Chang; Shyi-Jou Chen; Chih-Chien Wang; Wen-Tsung Lo (Journal of Medical Sciences, 2022)
Morganella morganii is a rare cause of neonatal infections, and early-onset neonatal sepsis caused by M. morganii is serious and even fatal. We describe an extremely low birth weight female infant with early-onset M. morganii sepsis to highlight the importance of awareness of this potentially fatal organism.